The Effectiveness of Using Reels on Instagram Toward Students’ Vocabulary Mastery at Senior High School - Lia Puspitasari (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
Vocabulary is the basic component of English that must be learned by students who use English as second language. Mastering English vocabulary will help the students to improve four language skills such as listening, reading, speaking, and writing. To master vocabulary, the students can read English book, watch English movie, or listen to English songs. In this digital era, students can enrich their vocabulary through social media. One of the popular social media is Instagram through reels feature. Reels can help students to gain and to understand the vocabulary because many Indonesian content creators share their knowledge about English and explain it using bahasa Indonesia clearly. The purpose of this study was to find out the effectiveness of using reels on Instagram to enhance students’ vocabulary mastery at the first-grade students of MAN 1 Madiun. The researcher was formulated the research problem as follows: “Is there any significant difference on students’ vocabulary mastery before and after being taught by using reels on Instagram at the firs- grade students of MAN 1 Madiun?”. In this study, the researcher was using quantitative approach with pre-experimental research method. The population of this study was the first-grade students of MAN 1 Madiun. The sample of this study were 35 students which selected by using purposive sampling technique. The instrument of this study is vocabulary test consist of 20 questions for short answer and 10 questions for true-or false. The test was given twice in pre-test and post-test. After conducting the both test, the researcher analysed the data using SPSS 16.0 with the formula paired sample t-test to know the difference of mean scores of the pre-test and post-test.